A comunicação da equipe de enfermagem com o paciente traqueostomizado - Gaspar, Maria do Rocio de Faria (2014)
INTRODUCTION: In hospital settings, communication takes on a therapeutic aspect. Therapeutic communication results from closer ties between the nursing team and patients. OBJECTIVE: The present study aims to identify nursing teams needs in communication, admittance and caring actions towards tracheostomized patients in order to help them in their recovery. METHODOLOGY: this research was carried out from a descriptive exploratory study, quantitative, qualitative approach, held among 51 nursing team members (nursing assistants, technicians and nurses) of Hospital de Clnicas/UFPR, Curitiba, Paraná State/Brazil in its Female and Male Wards, Adult Step-Down Unit (SDU) and ICU, and Neurosurgical Ward, among professionals between 30 and 50 years of age, working directly with tracheostomized patients, more than 10 years of professional practice. The study was performed after the application of a questionnaire with 10 combined open and closed questions. RESULTS: Research results evidenced that the participants have varied experience in their professional area, and in their daily work routine, they observed the need and importance of interaction with tracheostomized patients; thus, it is highly significant to keep the communication with patients during caring practice. In the study, it was evidenced that 93.1% of the nursing assistants, 83.3% of the nursing technicians and 57.1% of the nurses were instructed in relation to the communication practice with the tracheostomized during their qualification or daily nursing practice. Data point out that Nursing Assistants and Technicians had more instructions than nurses (p=0.028). Gaps in the process of the participants qualification were evidenced in the study as none of the categories reached 100% in relation to instructions on tracheostomized patients care. CONCLUSIONS: Information evidenced by the study shows the need of improving qualification and training in the researched institution aiming to accomplish communication, admittance and care to tracheostomized patients.